2021
DOI: 10.3390/proteomes9010015
|View full text |Cite
|
Sign up to set email alerts
|

Proteome Discoverer—A Community Enhanced Data Processing Suite for Protein Informatics

Abstract: Proteomics researchers today face an interesting challenge: how to choose among the dozens of data processing and analysis pipelines available for converting tandem mass spectrometry files to protein identifications. Due to the dominance of Orbitrap technology in proteomics in recent history, many researchers have defaulted to the vendor software Proteome Discoverer. Over the fourteen years since the initial release of the software, it has evolved in parallel with the increasingly complex demands faced by prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
118
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 167 publications
(118 citation statements)
references
References 77 publications
0
118
0
Order By: Relevance
“…The spectra used in this evaluation were from 12 instrument runs: six from a 2 ng sample which approximates 10 cells and six from a 0.2 ng sample which approximates 1 cell (see Methods). We benchmark 5 commonly used peptide identification tools: MetaMorpheus 8 , MsFragger 9 , MSGF+ 10 , MaxQuant 11 , and Proteome Discoverer 12 .…”
Section: Resultsmentioning
confidence: 99%
“…The spectra used in this evaluation were from 12 instrument runs: six from a 2 ng sample which approximates 10 cells and six from a 0.2 ng sample which approximates 1 cell (see Methods). We benchmark 5 commonly used peptide identification tools: MetaMorpheus 8 , MsFragger 9 , MSGF+ 10 , MaxQuant 11 , and Proteome Discoverer 12 .…”
Section: Resultsmentioning
confidence: 99%
“…In versions 1.0–2.0, the protein group is assigned to the protein with the highest total percentage coverage. In versions 2.1 onward, the largest protein in a group bearing equivalent evidence to all other proteins is assigned [ 17 ]. A recent analysis of 22 search engines demonstrated that resulting protein lists change little from the same MS/MS evidence [ 18 ], and therefore the two will be considered as equivalent in this light reanalysis.…”
Section: Methodsmentioning
confidence: 99%
“…There are many software platforms that enable MS/MS-based de novo and/or DB search enginebased identification (Box 4; e.g., MaxQuant [95], PEAKS [96], MS-GF+ [97], MSFragger [98], and Proteome Discoverer [99]). However, only a few computational MS tools are currently available that have been specifically designed for antibody proteomics data (e.g., PASA [100] and PEAKS AB 2.0 [101]).…”
Section: Computational Considerations For Ab-seqmentioning
confidence: 99%